The Impact of The Labor Force in The South – East Region During The COVID-19 Crisis - Daniela – Lavinia BALASAN; Florin – Marian BUHOCIU; Cristinel FERȚU (Communications of International Proceedings, 2021)
The notion of development involves the versification and analysis of activities, boosting investment, but also activities that have as final goal, increasing the standard of living of people. Regional development is the set of activities and initiatives to be addressed in order to ensure sustainable economic growth.  In writing this article, we analysed and studied data and information specific to the South – East Region, especially during the period we are in, namely during the covid-19 pandemic. The main purpose of this article is to highlight precisely the real problems facing the region by studying the impact of the economic system.  At the same time, we will debate the crisis caused by the COVID-19 pandemic and its problems with the South-East labour market.
Keywords: development; rural; analysis; labour force; pandemic